The Proteome of Biologically Active Membrane Vesicles from Piscirickettsia salmonis LF-89 Type Strain Identifies Plasmid-Encoded Putative Toxins - Oliver, Cristian; Hernández, Mauricio A.; Tandberg, Julia I.; Valenzuela, Karla N.; Lagos, Leidy X.; Haro, Ronie E.; Sánchez, Patricio; Ruiz, Pamela A.; Sanhueza-Oyarzún, Constanza; Cortés, Marcos A.; Villar, María T.; Artigues, Antonio; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Piscirickettsia salmonis is the predominant bacterial pathogen affecting the Chilean salmonid industry. This bacterium is the etiological agent of piscirickettsiosis, a significant fish disease. Membrane vesicles (MVs) released by P. salmonis deliver several virulence factors to host cells. To improve on existing knowledge for the pathogenicity-associated functions of P. salmonis MVs, we studied the proteome of purified MVs from the P. salmonis LF-89 type strain using multidimensional protein identification technology. Initially, the cytotoxicity of different MV concentration purified from P. salmonis LF-89 was confirmed in an in vivo adult zebrafish infection model. The cumulative mortality of zebrafish injected with MVs showed a dose-dependent pattern. Analyses identified 452 proteins of different subcellular origins; most of them were associated with the cytoplasmic compartment and were mainly related to key functions for pathogen survival. Interestingly, previously unidentified putative virulence-related proteins were identified in P. salmonis MVs, such as outer membrane porin F and hemolysin. Additionally, five amino acid sequences corresponding to the Bordetella pertussis toxin subunit 1 and two amino acid sequences corresponding to the heat-labile enterotoxin alpha chain of Escherichia coli were located in the P. salmonis MV proteome. Curiously, these putative toxins were located in a plasmid region of P. salmonis LF-89. Based on the identified proteins, we propose that the protein composition of P. salmonis LF-89 MVs could reflect total protein characteristics of this P. salmonis type strain.